Green Business Strategies: Profitability Through Sustainable Practices - Sharma, Vishal (Journal of Global Economy, Business and Finance, 2026)
Green businesses or sustainable businesses are economic opportunities that have minimal negative impact and potential positive impacts on the environment, community, society and economy, and such business ventures also strive to enhance the bottom line. Furthermore, the global net-zero 2050 challenge involves decreasing worldwide carbon dioxide emissions to net zero by 2050, along with endeavors to restrict the long-term rise in average global temperatures to 1.5˚C. This consequently impacts business activities which cause environmental damage, hence, leading to the transformation in the economic impacts on product demand, capital allotment, expenses and job opportunities across energy and land-use strategies. This report highlights the virtues associated with green businesses, varied types of green business initiatives and the concept of green marketing. Going deeper into green business strategies, it further discusses the global concern of drowning in plastic pollution associated with single-use plastic packaging, suggesting sustainability views on reusable packaging options and bringing to attention various options related to the scientific disposal of hazardous industrial waste, thereby diminishing the emissions of toxic and greenhouse gases, and decreasing environmental pollution. The white paper concludes with the obstacles green businesses encounter to achieve the net zero 2050 scenario - the transitional challenge.